Comparison of Culture, Social-Economics, Attitude and Behavior of Diabetes Mellitus Patients Between Urban and Rural of Southeast Sulawesi (Public Health Perspective Journal, 2019)
Diabetes mellitus is a serious health problem; the incidence of diabetes mellitus tends to increase, from 6.9% in 2013 to 8.5% in 2018. The difference in prevalence of diabetes mellitus in urban area is 14.7% and rural 7.2% by influenced lifestyle changes. The purpose of this study was to distinguish between culture, socio-economics, attitudes and behaviour of people with type 2 diabetes mellitus in urban and rural communities in Southeast Sulawesi, especially Kendari City and Konawe Islands. This research was a quantitative research, with a cross sectional approach. The research sample was 130 respondents with cluster techniques. Instrument used a questionnaire sheet. Data collection techniques were in form of interviews, observations and documentation. Analysis of calculations in this study used Mann Whitney and found that there were differences in cultural variables (p = 0,000), socioeconomic (p = 0,000), attitudes (p = 0,000) and behaviour (p = 0,000) in type 2 diabetes mellitus in urban and rural communities. The results shows that the incidence of type 2 diabetes mellitus is more increased in urban areas than rural areas due to food habit, socio-economic, attitudes, behaviour and as a consideration to improve health status by maintaining a healthy lifestyle such as exercise and nutritious food.